Porous titanium dioxide composite material with plasma resonance effect as well as preparation method and photo-thermal synergistic catalytic hydrogen production application of porous titanium dioxide composite material

The porous titanium dioxide particles are synthesized through the solvent thermal method and the light sedimentation method loads metal CU to build a Schottky knot to form a porous titanium dioxide composite material with a plasma resonance effect. Catalytic hydrogen production performance.

CN119327453APending Publication Date: 2025-01-21SHENZHEN RES INST OF WUHAN UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411419589.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

In the existing photocatalytic cracking hydrogen production technology, the wide band gap of TiO2 leads to low solar energy utilization and insufficient catalytic activity, and traditional synthesis methods have problems such as time-consuming and uneven material morphology.

Method used

The solvent thermal method is used to synthesize the porous titanium dioxide particles P-TIO2, and through the light sedimentary load metal CU to build a Schottky knot to form a porous titanium dioxide composite material CU/P-TIO2 with a plasma resonance effect.

Benefits of technology

The light absorption range, catalytic activity, and light thermal conversion efficiency are significantly improved, and the hydrogen production performance is improved, and the hydrogen production rate can reach 47.6 mmol G-1H-1.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005080385050000011
    Figure HDA0005080385050000011
  • Figure HDA0005080385050000012
    Figure HDA0005080385050000012
  • Figure HDA0005080385050000021
    Figure HDA0005080385050000021
Patent Text Reader

Abstract

A preparation method of the porous titanium dioxide composite material comprises the following steps: 1) adding tetrabutyl titanate into glacial acetic acid while stirring until a solution is stirred to be white, so as to obtain a mixture; (2) transferring the mixture obtained in the step (1) into a drying oven, heating for a period of time, cooling at room temperature, centrifuging and drying to obtain porous titanium dioxide particles P-TiO2; and 3) dispersing the titanium dioxide particles P-TiO2 obtained in the step 2) in pure water, performing ultrasonic treatment until the titanium dioxide particles are uniformly dispersed, adding a certain amount of copper acetate solution, performing photodeposition under irradiation, and then performing centrifugation and drying to obtain the porous titanium dioxide composite material (Cu / P-TiO2) with the plasma resonance effect. The preparation method comprises the following steps: firstly, synthesizing titanium dioxide particles P-TiO2 with a porous structure by adopting a simple solvothermal method, then carrying out photodeposition treatment on the P-TiO2, loading metal Cu, successfully constructing a Schottky junction between the P-TiO2 and the metal Cu, obtaining the porous titanium dioxide composite material Cu / P-TiO2 with a plasma resonance effect, increasing exposure of active sites, and improving the photocatalytic activity of the porous titanium dioxide composite material Cu / P-TiO2. Compared with traditional titanium dioxide, the photocatalyst has a larger light absorption range, the catalytic activity and the photo-thermal conversion efficiency are effectively improved, and the hydrogen production performance is excellent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of photothermal synergistic catalytic cracking of water to produce hydrogen, and in particular to a preparation method and application of a porous titanium dioxide composite material with a plasma resonance effect. Background Art

[0002] Photocatalytic water splitting to produce hydrogen has emerged as an effective method to use solar energy to drive water decomposition into hydrogen energy, and has attracted widespread attention from researchers. However, due to the limitations of scientific theory and production development, the current photocatalytic production efficiency and economic value are still low, and in most situations it still cannot replace traditional fossil energy.

[0003] At present, semiconductor TiO2 is widely used in photocatalytic hydrogen evolution due to its high corrosion resistance and good chemical stability. However, the wide band gap of TiO2 leads to its narrow light absorption range, resulting in low solar energy utilization, which limits its practical application. In recent years, researchers have proposed many strategies to improve the photocatalytic performance of TiO2, such as element doping. Although they can effectively narrow the band gap of TiO2, they cannot significantly improve the catalytic activity. In the prior art, there are also reports on composite materials with metals deposited on the surface of titanium dioxide, but they are mainly steam reduction and solvothermal methods, which have the disadvantages of long time consumption and uneven material morphology and element distribution, which increase the difficulty of the operation steps and the synthesis cost. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a method for preparing a porous titanium dioxide composite material with a plasma resonance effect in view of the deficiencies in the above-mentioned prior art. Compared with traditional titanium dioxide, it has a larger light absorption range, and the catalytic activity and photothermal conversion efficiency are effectively improved, and the hydrogen production performance is excellent.

[0005] The technical solution adopted by the present invention to solve the above-mentioned problems is:

[0006] A porous titanium dioxide composite material with plasma resonance effect, the preparation method of which comprises the following steps:

[0007] 1) adding tetrabutyl titanate into glacial acetic acid while stirring until the solution turns white to obtain a mixture;

[0008] 2) placing the mixture obtained in step 1) into an oven for heating for a period of time, cooling to room temperature, centrifuging and drying to obtain porous titanium dioxide particles P-TiO2;

[0009] 3) The titanium dioxide particles P-TiO2 obtained in step 2) are dispersed in pure water, ultrasonicated until uniformly dispersed, a certain amount of copper acetate solution is added, and photodeposition is performed under irradiation, followed by centrifugation and drying to obtain a porous titanium dioxide composite material (abbreviated as Cu / P-TiO2) with a plasma resonance effect.

[0010] According to the above scheme, in step 1), the volume ratio of glacial acetic acid to tetrabutyl titanate is (40-60):1.

[0011] According to the above scheme, in step 1), the stirring temperature is room temperature, the stirring rate is 100 to 1500 r / min, and the stirring time after the tetrabutyl titanate is added dropwise is 10 to 20 minutes.

[0012] According to the above scheme, in step 2), the oven is heated at a temperature of 175-185° C. for 20-30 h, preferably at a temperature of 180° C. for 24 h.

[0013] According to the above scheme, in step 2), the drying temperature is 50-70°C and the time is 6-9h.

[0014] According to the above scheme, in step 3), the concentration of titanium dioxide particles P-TiO2 added to pure water is 1-2 mg / mL; the mass ratio of titanium dioxide particles P-TiO2 to copper in copper acetate solution is 100:(0.5-1.5); the concentration of copper acetate solution itself is in the range of 3-5 mol / L.

[0015] According to the above scheme, in step 3), the photodeposition conditions are: stirring at room temperature, a stirring rate of 100 to 1000 r / min, a xenon lamp as the irradiation light source, and a photodeposition time of 1.5 to 2.5 h.

[0016] According to the above scheme, in step 3), the drying temperature is 50-70°C and the time is 6-9h.

[0017] The porous titanium dioxide composite material with plasma resonance effect prepared by the above method is anatase phase, and its morphology is characterized by rice-like ellipsoids, the long diameter of the ellipsoids is 1.6-2.0 μm, the short diameter is 0.8-1.2 μm, and it has a porous structure and surface hydroxyl groups.

[0018] The porous titanium dioxide composite material with plasma resonance effect prepared by the above method is used as a photothermal catalyst in catalytic hydrogen production, especially in the photothermal synergistic catalytic decomposition of pure water to produce hydrogen.

[0019] The technical concept of the present invention is mainly as follows:

[0020] The present invention adopts a simple solvothermal method to first obtain rice-grain titanium dioxide P-TiO2 with a porous structure. On the one hand, the formation of the porous structure provides a larger specific surface area, which helps to increase the contact area between the photocatalyst and the reactant, thereby improving the photocatalytic activity; on the other hand, the porous structure helps to separate and transport photogenerated charges, and photogenerated electrons and holes can be effectively separated in the pores, reducing recombination and improving photocatalytic efficiency.

[0021] Then, the present invention uses a photodeposition method to successfully load metal Cu on P-TiO2, thereby constructing a Schottky junction. The successful loading of Cu does not change the physical structure and morphological characteristics of P-TiO2, and a small amount of Cu occupies part of the pore space, and finally forms a porous titanium dioxide composite material with a plasma resonance effect. The composite material has a surface plasma resonance effect, and after being excited by light, hot carriers will be generated, which promotes energy transfer and conversion, thereby accelerating the photothermal synergistic catalytic reaction rate. This synthesis method of the present invention has the advantages of simple operation, low cost and stable crystal structure.

[0022] Unlike traditional titanium dioxide materials, the titanium dioxide composite material prepared by the present invention contains a porous structure, which provides more active sites, is conducive to the effective separation of photogenerated electrons and holes, and improves the efficiency of photocatalytic reactions; moreover, the successful loading of Cu forms a Schottky junction, effectively narrows the band gap of the titanium dioxide catalyst, broadens the light absorption range, and enhances the reaction activity. In addition, the dispersed loading of Cu enables the surface plasma effect to obtain the strongest photothermal effect conversion under the Cu / P-TiO2 composite system, thereby greatly improving the photothermal synergistic catalytic activity of the titanium dioxide catalyst.

[0023] The porous titanium dioxide composite material with plasma resonance effect described in the present invention also has a surface hydroxyl structure. The surface hydroxyl structure can effectively improve the hydrophilicity of the material and increase the adsorption energy of hydrogen ions, thereby improving its activity as a photothermal catalyst in water or aqueous solution. Therefore, the titanium dioxide composite material prepared by the present invention can exhibit excellent photocatalytic performance as a photothermal catalyst in pure water.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] The porous titanium dioxide composite material with plasma resonance effect provided by the present invention first adopts a simple solvent thermal method to synthesize titanium dioxide particles P-TiO2 with a porous structure, and then performs photodeposition treatment on P-TiO2 to load metal Cu, successfully constructs a Schottky junction between P-TiO2 and metal Cu, and obtains a porous titanium dioxide composite material Cu / P-TiO2, which increases the specific surface area of ​​the material, increases the exposure of active sites, and has a surface plasma resonance effect. Therefore, compared with traditional titanium dioxide, the titanium dioxide composite material prepared by the present invention has a larger light absorption range, better photogenerated carrier separation ability and hot carrier generation efficiency, better catalytic activity and higher photothermal conversion efficiency under photothermal synergy conditions, good photothermal catalytic performance, and a hydrogen production rate of up to 47.6mmol g under a fixed period. -1 h -1 . BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 XRD characterization diagram of Cu / P-TiO2 prepared in Example 1;

[0027] Figure 2 The SEM image of Cu / P-TiO2 prepared in Example 1;

[0028] Figure 3 BET spectrum of Cu / P-TiO2 prepared in Example 1;

[0029] Figure 4 FT-IR test chart of Cu / P-TiO2 prepared in Example 1;

[0030] Figure 5 The catalytic performance diagram of the Cu / P-TiO2 prepared in Example 1 for photocatalytic decomposition of pure water to produce hydrogen;

[0031] Figure 6 The catalytic performance diagram of the photothermal synergistic catalytic decomposition of pure water to produce hydrogen by Cu / P-TiO2 prepared in Example 1;

[0032] Figure 7 The catalytic performance diagram of the photothermal synergistic catalytic decomposition of pure water to produce hydrogen by P-TiO2 prepared in the comparative example;

[0033] Figure 8 The catalytic performance diagram of the photothermal synergistic catalytic decomposition of pure water to produce hydrogen by Cu / P-TiO2 prepared in Example 2;

[0034] Fig. 9 This is the catalytic performance diagram of the Cu / P-TiO2 prepared in Example 3 for the photothermal synergistic catalytic decomposition of pure water to produce hydrogen. DETAILED DESCRIPTION

[0035] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the present invention is not limited to the following embodiments.

[0036] In the following examples, the concentration of the copper acetate solution is 4 mol / L; the centrifugal conditions are: a centrifugal rate of 10000 r / min, 3 to 5 centrifugal times, and a single centrifugal time of 5 to 8 min; and the drying conditions are: a drying temperature of 60° C. and a drying time of 6 to 9 h.

[0037] Example 1

[0038] A porous titanium dioxide composite material with plasma resonance effect, the specific steps of the preparation method are as follows:

[0039] 1) Stir 10 mL of glacial acetic acid at room temperature, quickly add 0.2 mL of tetrabutyl titanate solution during stirring, and continue stirring at a stirring rate of 1000 r / min for 15 min to obtain a white mixture;

[0040] 2) The mixture obtained in step 1) is transferred into an oven, heated at 180° C. for 24 h, cooled to room temperature, and then centrifuged and dried to obtain titanium dioxide particles P-TiO2 having a porous structure;

[0041] 3) Disperse 0.1 g of P-TiO2 in step 2) in 60 mL of ultrapure water, ultrasonicate for 2 min until evenly dispersed, dropwise add copper acetate solution so that the mass ratio of P-TiO2 to Cu is 100:1, and photodeposit under xenon lamp for 2 h at room temperature with stirring. After centrifugation and drying, a porous titanium dioxide composite material (Cu / P-TiO2) with plasma resonance effect is obtained.

[0042] like Figure 1 As shown, the XRD spectrum of the porous titanium dioxide composite material with plasma resonance effect prepared in this embodiment shows the characteristic peak of TiO2 in the XRD curve, which proves that the crystalline phase of TiO2 has not changed before and after photodeposition, and the loading of metallic copper has no adverse effect on the crystalline phase of P-TiO2, which proves the rationality of the photodeposition method.

[0043] Figure 2 This is the SEM image of the porous titanium dioxide composite material with plasma resonance effect prepared in this embodiment. The ellipsoidal shape presented in the SEM image shows that Cu / P-TiO2 has a uniform rice-grain particle structure with a long diameter of 1.6-2.0μm and a short diameter of 0.8-1.2μm, confirming the successful synthesis of the particle structure.

[0044] Figure 3The BET diagram of the porous titanium dioxide composite material with plasma resonance effect prepared in this embodiment shows that a very small hysteresis loop appears in the curve, indicating the existence of mesopores (2nm<pore size<10nm) in Cu / P-TiO2, proving its porous structure, which is brought about by the solvothermal preparation of P-TiO2.

[0045] Figure 4 The FT-IR spectrum of the porous titanium dioxide composite material with plasma resonance effect prepared in this example shows that Cu / P-TiO2 has a peak at 3400 cm -1 and 1630cm -1 There is an absorption peak at 3400cm -1 1630cm -1 The absorption peaks at correspond to the stretching vibration and bending vibration of the hydroxyl group respectively. The porous titanium dioxide synthesized by the solvothermal method has surface hydroxyl functional groups, and after loading metal Cu, the surface hydroxyl functional groups still exist.

[0046] The experimental steps for photocatalytic decomposition of pure water to produce hydrogen are as follows: 20 mg of photocatalyst (i.e., the porous titanium dioxide composite material with plasma resonance effect prepared in the example) is dispersed in 80 mL of aqueous solution containing 50 mL of H2O, 30 mL of methanol and 52 μL of H2PtCl6 (10 mmol / L), and then the mixed solution is sealed in a quartz container, and the dissolved oxygen and other gases in the system are removed by a vacuum pump for 10 minutes. The distance between the xenon lamp and the reaction solution is kept at 20 cm, and the current of 16 A is maintained for 3 hours, and then the hydrogen production of the photocatalyst is obtained by gas chromatography. Figure 5 As shown in the figure, the hydrogen production rate of Cu / P-TiO2 prepared in the embodiment can reach 11.8mmol g during 3h of illumination in pure water environment. -1 h -1 , showing a higher level of hydrogen evolution.

[0047] The experimental steps of photothermal synergistic catalytic decomposition of pure water to produce hydrogen are the same as those of photocatalytic decomposition of pure water to produce hydrogen, except that 80°C circulating water is connected to the outside of the container. Figure 6 As shown in the figure, the hydrogen production rate of Cu / P-TiO2 prepared in the embodiment can reach 47.6mmol g under 80℃ environment during 3h illumination. -1 h -1 Compared with the performance at room temperature, it is improved by 4 times, which means that the photothermal conversion efficiency is significantly improved under the photothermal synergy conditions.

[0048] Comparative Example

[0049] A titanium dioxide particle material, the specific steps of the preparation method are as follows:

[0050] 1) Stir 10 mL of glacial acetic acid at room temperature, quickly add 0.2 mL of tetrabutyl titanate solution during stirring, and continue stirring at a stirring rate of 1000 r / min for 15 min to obtain a white mixture;

[0051] 2) The mixture obtained in step 1) is transferred into an oven, heated at 180° C. for 24 h, cooled to room temperature, and then centrifuged and dried to obtain titanium dioxide particles P-TiO2.

[0052] The experimental steps of the photocatalytic decomposition of pure water to produce hydrogen by the titanium dioxide particles prepared in this comparative example are consistent with the photocatalytic decomposition of pure water to produce hydrogen in Example 1. The hydrogen production rate of the P-TiO2 prepared in the comparative example under pure water environment during 3 hours of illumination is 2.8 mmol g -1 h -1 . Figure 7 The catalytic performance diagram of the titanium dioxide particles prepared in this comparative example for the photothermal catalytic decomposition of pure water to produce hydrogen is shown in FIG. The experimental steps are consistent with the photothermal catalytic decomposition of pure water to produce hydrogen experiment in Example 1, and the illumination time is 3 hours. Figure 7 It can be seen that the hydrogen production rate of P-TiO2 prepared in the comparative example can reach 6.2mmol g under pure water environment during 3h illumination. -1 h -1 , which is only 13% of the photothermal conversion efficiency of Cu / P-TiO2, significantly lower than the performance of Cu / P-TiO2 prepared in the example. Explanation: Compared with traditional titanium dioxide, the porous titanium dioxide composite material with plasma resonance effect prepared in the present invention significantly improves its performance as a photothermal catalyst.

[0053] Example 2

[0054] A porous titanium dioxide composite material with plasma resonance effect, the specific steps of the preparation method are as follows:

[0055] 1) Stir 10 mL of glacial acetic acid at room temperature, quickly add 0.2 mL of tetrabutyl titanate solution during stirring, and continue stirring at a stirring rate of 1000 r / min for 15 min to obtain a white mixture;

[0056] 2) transferring the mixture obtained in step 1) into an oven, heating at 180° C. for 22 h, cooling to room temperature, centrifuging and drying to obtain titanium dioxide particles P-TiO2 having a porous structure;

[0057] 3) Disperse 0.1 g of P-TiO2 in step 2) in 50 mL of ultrapure water, ultrasonicate for 3 min until evenly dispersed, dropwise add copper acetate solution so that the mass ratio of P-TiO2 to Cu is 100:0.5, and photodeposit under xenon lamp for 2 h at room temperature with stirring. After centrifugation and drying, a porous titanium dioxide composite material (Cu / P-TiO2) with plasma resonance effect is obtained.

[0058] Figure 8 The catalytic performance diagram of the photothermal synergistic catalytic decomposition of pure water to produce hydrogen by the porous titanium dioxide composite material (Cu / P-TiO2) with plasma resonance effect prepared in Example 2 is consistent with the photothermal synergistic catalytic decomposition of pure water to produce hydrogen in Example 1, and the illumination time is 3h. Figure 8 It can be seen that the porous titanium dioxide composite material with plasma resonance effect prepared in Example 2 can produce hydrogen at a rate of 30.8 mmol g under pure water environment during 3 h of illumination. -1 h -1 .

[0059] Example 3

[0060] A porous titanium dioxide composite material with plasma resonance effect, the specific steps of the preparation method are as follows:

[0061] 1) Stir 12 mL of glacial acetic acid at room temperature, quickly add 0.2 mL of tetrabutyl titanate solution during stirring, and continue stirring at a stirring rate of 1000 r / min for 20 min to obtain a white mixture;

[0062] 2) transferring the mixture obtained in step 1) into an oven, heating at 175° C. for 26 h, cooling to room temperature, centrifuging and drying to obtain titanium dioxide particles P-TiO2 having a porous structure;

[0063] 3) Disperse 0.1 g of P-TiO2 in step 2) in 80 mL of ultrapure water, ultrasonicate for 4 min until uniformly dispersed, add copper acetate solution dropwise so that the mass ratio of P-TiO2 to Cu is 100:1.5, and photodeposit under xenon lamp for 2.5 h under room temperature stirring conditions. After centrifugation and drying, a porous titanium dioxide composite material (Cu / P-TiO2) with plasma resonance effect is obtained.

[0064] Fig. 9 The catalytic performance diagram of the photothermal synergistic catalytic decomposition of pure water to produce hydrogen by the porous titanium dioxide composite material (Cu / P-TiO2) with plasma resonance effect prepared in Example 3 is consistent with the photothermal synergistic catalytic decomposition of pure water to produce hydrogen in Example 1, and the illumination time is 3h. Fig. 9It can be seen that the porous titanium dioxide composite material with plasma resonance effect prepared in Example 3 can produce hydrogen at a rate of 28.1 mmol g under pure water environment during 3 h of illumination. -1 h -1 .

[0065] The above is only a preferred embodiment of the present invention. It should be pointed out that a person skilled in the art can make several improvements and changes without departing from the creative concept of the present invention, which all belong to the protection scope of the present invention.

Claims

1. A porous titanium dioxide composite material with plasma resonance effect, characterized in that: The titanium dioxide composite material is a copper-loaded titanium dioxide particle material, which is an anatase phase and has a rice-grain-shaped ellipsoidal morphology. The ellipsoidal ellipsoid has a long diameter of 1.6 to 2.0 μm and a short diameter of 0.8 to 1.2 μm, and has a porous structure and surface hydroxyl groups. The mass ratio of titanium dioxide to copper is (50 to 150):

1.

2. A method for preparing a porous titanium dioxide composite material having a plasma resonance effect, characterized in that: The steps include: 1) adding tetrabutyl titanate into glacial acetic acid while stirring until the solution turns white to obtain a mixture; 2) placing the mixture obtained in step 1) into an oven for heating for a period of time, cooling to room temperature, centrifuging and drying to obtain porous titanium dioxide particles; 3) The titanium dioxide particles obtained in step 2) are dispersed in solvent water, ultrasonicated until uniformly dispersed, and then a copper acetate solution is added to perform photodeposition under irradiation, followed by centrifugation and drying to obtain a porous titanium dioxide composite material with a plasma resonance effect.

3. The method for preparing a porous titanium dioxide composite material having a plasma resonance effect according to claim 2, characterized in that: In step 3), the concentration of titanium dioxide particles added to pure water is 1-2 mg / mL; the mass ratio of titanium dioxide particles to copper in the copper acetate solution is 100:(0.5-1.5); and the concentration of the copper acetate solution itself is in the range of 3-5 mol / L.

4. The method for preparing a porous titanium dioxide composite material having a plasma resonance effect according to claim 2, characterized in that: In step 3), the photodeposition conditions are: stirring at room temperature, a stirring rate of 100 to 1000 r / min, a xenon lamp as the irradiation light source, and a photodeposition time of 1.5 to 2.5 h.

5. The method for preparing a porous titanium dioxide composite material with a plasma resonance effect according to claim 2, characterized in that: In step 2), the oven is heated to a temperature of 175 to 185° C. for 20 to 30 hours.

6. The method for preparing a porous titanium dioxide composite material having a plasma resonance effect according to claim 2, characterized in that: In step 1), the volume ratio of glacial acetic acid to tetrabutyl titanate is (40-60):

1.

7. Use of the porous titanium dioxide composite material with plasma resonance effect as claimed in claim 1 as a photothermal catalyst in decomposing pure water to produce hydrogen.